Immunosuppressive Amino-Acid Catabolizing Enzymes in Multiple Sclerosis - Correale, Jorge (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease that affects the central nervous system. mediated mainly, but not exclusively, by Th1, Th17, and B lymphocytes. When immune cells are activated by inflammatory and antigenic cues, their demand for AA rapidly increases. Although AA deprivation per se may attenuate immune responses under some conditions, cells also possess AA-sensing pathways that trigger profound changes in cell metabolism, in response to changes in AA levels. Data show that cells expressing enzymes that degrade AA, modulate antigen-presenting cell and lymphocyte function, revealing AA pathways as critical in controlling immune cell gene expression, function, and survival. Basal AA catabolism may contribute to immune homeostasis preventing autoimmunity, whereas elevated AA catalytic activity may reinforce immune suppression. Furthermore, accumulating evidence shows that several downstream AA metabolites are important biological mediators of autoimmune response regulation. Two of the most important AA that modulates the immune response are L-Tryptophan (Trp) and L-Arginine (Arg). Tryptophan is catabolized through 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO) 1 and IDO2 enzymes, while three other enzymes catabolize Arg: inducible nitric oxide synthetase (iNOS), and two arginase isoforms (ARG1, ARG2). Genes encoding IDO, iNOS, and ARG are induced by inflammatory cues such as cytokines, a key feature that distinguishes them from enzymes that catabolize other AA. Evidence suggests that AA catabolism is decreased in MS patients and that this decrease has functional consequences, increasing pro-inflammatory cytokines and decreasing Treg cell numbers. These effects are mediated by at least two distinct pathways involving serine/threonine kinases: the general control non-repressed 2 (GCN2) pathway; and the mammalian target of rapamycin (mTOR) pathway. Similarly, IDO-deficient mice show experimental autoimmune encephalomyelitis (EAE) exacerbation with increased Th1 and Th17 cells, as well as reduction of Treg cells. In contrast, administration of the downstream Trp metabolite 3-HAA, inhibits effector Th1 and Th17 cells, ameliorating EAE by promoting Treg responses through upregulation of TGF-β production by dendritic cells. Overall, these observations highlight the importance of AA catabolism in the modulation of immunological responses in MS patients. Molecules involved in these pathways warrant further exploration as potential new therapeutic targets in MS.